Potential molecular targets for intervention in pelvic organ prolapse - Wu, Xia; Liu, Xiaochun; Li, Tingting (Frontiers in Medicine, 2023)
Pelvic organ prolapse (POP) is a concerning gynecological benign illness in middle-aged and senior women. Its etiology is complex, the incidence rate is high, symptoms are clinically subjective, and its influence tends to be polarized. At present, for those who need medical treatment, whether surgical or non-surgical, complications cannot be ignored, and the treatment effect needs to be optimized. However, there is a lack of accurate micro-molecular biological intervention in the prevention, diagnosis, delay, and treatment of POP. This text reviews the state-of-the-art of micro-mechanism POP etiology. The molecular mechanisms between POP and MMPs/TIMPs (matrix metal peptidases/tissue inhibitors of metalloproteinase), cyclins, microRNAs, other cytokines, oxidative stress, inflammatory reaction, and estrogen are discussed, and relevant molecular targets that may intervene in the current situation of POP are summarized. The aim of this study is to provide more accurate potential biomarkers or molecular targets for the prevention, diagnosis, delay, and treatment of POP, optimize the current situation of POP. In the future, continued research is needed to identify other mechanisms that contribute to POP